Elevated radium levels in Nubian Aquifer groundwater of Northeastern Africa - Mahmoud I. Sherif (Nature Portfolio, 2021)
Abstract The Nubian Sandstone Aquifer System in Northeast Africa and the Middle East is a huge water resource of inestimable value to the population. However, natural radioactivity impairs groundwater quality throughout the aquifer posing a radiological health risk to millions of people. Here we present measurements of radium isotopes in Nubian Aquifer groundwater from population centers in the Western Desert of Egypt. Groundwater has 226Ra and 228Ra activities ranging from 0.01 to 2.11 and 0.03 to 2.31 Bq/L, respectively. Most activities (combined 226Ra + 228Ra) exceed U.S. EPA drinking water standards. The estimated annual radiation doses associated with ingestion of water having the highest measured Ra activities are up to 138 and 14 times the WHO-recommended maxima for infants and adults, respectively. Dissolved Ra activities are positively correlated with barium and negatively correlated with sulfate, while barite is approximately saturated. In contrast, Ra is uncorrelated with salinity. These observations indicate the dominant geochemical mechanisms controlling dissolved Ra activity may be barite precipitation and sulfate reduction, along with input from alpha-recoil and dissolution of aquifer minerals and loss by radioactive decay. Radium mitigation measures should be adopted for water quality management where Nubian Aquifer groundwater is produced for agricultural and domestic consumption.